SPECIALIST CLINIC REGISTRATION SYSTEM HOSPITAL TELUK INTAN - Ooi, Stephanie Chia Huai (Universiti Malaysia Sarawak (UNIMAS), 2019)
Records management is always a must in a business. A company must have a system for filling, storing and accessing their documents. In the past few years, most of the company records their data in a paper-based form, store in files and using labeling besides the file for the purpose of finding the document easier. As the technology growth, most of the people start to computerize their paper work because the digital records system can minimize cost, time, space, and human energy in managing the data. The purpose of this project is to develop a computerize Specialist Clinic Registration System for Hospital Teluk Intan, Perak. Hospital Teluk Intan do not have computerize system to register and store the patients’ data. This proposed system allows Hospital Teluk Intan to register patients and generate report. To accomplish the project objectives, Madam Azniyanti Suhani Binti Ahmad Mokhtar, the Head of Department of Information Technology Department has given her full co-operation by leading me to understand the workflows of the “One-Stop Center” and the specialist clinics. The system is design after reviewing three existing hospital registration system which are Patient Registration System, Hospital Seri Manjung, Registration System, Hospital Sungai Buluh and Patient Registration System, Hospital Taiping.